Estratégias de enfrentamento (Coping) no luto: uma possibilidade para a promoção de saúde - Gonçalves, Paulo César (2013)
Our current society has established culturally implicit mechanisms of denial of the death, doing it a prohibited topic. As a consequence, the mourning has become a more complex process and that in some cases unfolds to become a health problem. In these cases the mourning is called "complicated mourning". In his professional activity, physicians, nurses, psychologists and other health workers deal directly with death and grieving people, but do not always come properly prepared to act in this situation, even why it is not regarded important elements that can be used in supporting to the coping in mourning. This research is a descriptive study, with quantitative and qualitative approach, aimed to understand within a group of people in a situation of mourning, which elements could be considered as elements of supporting in the face of loss, and therefore elements of health promoters in the mourning process. The sample of this research was composed of 29 people in a situation of mourning between the ages of 23 and 73 years, of both sexes, and that are users of CRAS (Center of reference of Social Assistance), in the northern region of the municipality of Franca-SP, that were submitted to a questionnaire whose purpose was to know which elements the subject used for coping in mourning. The family and spirituality are highlighted in this scenario and are essential to avoid the complicated grief; however, such elements are still neglected by health professionals. Key words: Coping; Health Promotion; Social Support; Spirituality.